Rheumatoid arthritis 1st time presenting with bilateral pleural effusion- A rare presentation - Malakar, Sayan; Sharma, Kailash Nath; Rana, Abhinav; Sharma, Tarun (Indian Journal of Case Reports, 2019)
Rheumatoid arthritis is the most common chronic autoimmune disorder involving joints and extra-axial system. Varied presentations have been described in the literature. Pulmonary involvement is also common. Inflammatory pleural effusions are an uncommon complication and are rarely seen in about 2% to 5% of patients with rheumatoid arthritis. Here, we present an interesting case where the patient presented with bilateral pleural effusion early in the disease. On further evaluation of the patient and the pleural fluid, it was found to be consistent with pleural effusion secondary to rheumatoid arthritis. The patient responded to oral non-steroidal antiinflammatory drugs along with disease-modifying agents.